Pembelajaran Arthropoda Menggunakan Booklet Sebagai Sumber Belajar Mandiri Siswa Kelas X SMA/MA - Muhammad, Fadil; Muhiddin P, Muhiddin P; Adnan, Adnan (Biology Teaching and Learning, 2018)
Abstract.  This Research and Development (R and D) concerns on learning media development that can be used as an alternative learning source of booklet on the subject of animal world sub chapter arthropoda. The R and D’s model used Analyze, Design, Develop, Implement, Evaluate (ADDIE). Validity test obtained from two expert validators and Practicality test obtained from the using of media by teacher and students. The Develop stage of this study conducted by validating e-magazine for further be implemented on SMAN 5 Jeneponto, Class of X MIA3. The number of subjects comprised of 35 students. Data collected from interview, observation and questionnaire. The result of validity test showed the average of media feasibility percentage is  85%. While the subject matter feasibility gained 86%. Both of these result showed very decent category which was meant that the media is feasible to be used. The average of teacher and students respond gained 91% and 89,2 % respectively toward positive respond. From the point of feasibility which had been evaluated by validity and practical test, this study can be conclude that booklet is valid and practice learning media to be implemented in learning process. Keywords: booklet, interactive, validity, practicality, arthropoda